2020
DOI: 10.1039/d0ra06524b
|View full text |Cite
|
Sign up to set email alerts
|

A biotin-guided hydrogen sulfide fluorescent probe and its application in living cell imaging

Abstract: A biotin-guided hydrogen sulfide fluorescent probe has been shown clearly to possess the ability to target cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…A number of other functionalized NBDs lacking additional fluorophores have been reported as fluorescent sensors, often with turn-off responses. This signal change is likely due to residual and minimal fluorescence of the NBD-piperazine constructs or in less selectivity systems some signal in complex environments may be due to adventitious reaction with Cys or Hcy to generate fluorescent responses.…”
Section: Electrophilic H2s Probesmentioning
confidence: 99%
“…A number of other functionalized NBDs lacking additional fluorophores have been reported as fluorescent sensors, often with turn-off responses. This signal change is likely due to residual and minimal fluorescence of the NBD-piperazine constructs or in less selectivity systems some signal in complex environments may be due to adventitious reaction with Cys or Hcy to generate fluorescent responses.…”
Section: Electrophilic H2s Probesmentioning
confidence: 99%
“…In 2020, Zhang et al reported a biotin-guided fluorescent probe 2 . 24 The probe used biotin as a cancer-targeting group and piperazine-NBD as the recognition group of H 2 S, which has a sensitive response to H 2 S (Fig. 3a).…”
Section: Fluorescent Probes Targeting Cancer Receptorsmentioning
confidence: 99%
“…32 Biotin-containing molecules can be internalized selectively by cancer cells through receptor-mediated endocytosis and hence are used extensively in drug delivery and tumor-targeting imaging. 33,34 Therefore, we hypothesized that a biotin-guided H 2 S fluorescent probe could be used to image cancer cells selectively and efficiently.…”
Section: Introductionmentioning
confidence: 99%